Implementation of Query Optimization for Reducing Run Time Execution (International Journal of Advanced Research in Computer Science, 2017)
Query optimization is the process of selecting the most efficient query-evaluation plan from many strategies so, In this paper we have developed a technique that performs query optimization at compile-time to reduce the burden of optimization at run-time to improve the performance of the code execution. using histograms that are computed from the data and these histograms are used to get the estimate of selectivity for query joins and predicates in a query at compile-time. With these estimates, a query plan is constructed at compile-time and executed it at run-time.Keywords: compile time; optimal time; histogram; query optimization;